Matching the organic and inorganic counterparts during nucleation and growth of copper-based nanoparticles – in situ spectroscopic studies1. Issue 36 (28th September 2015) - Staniuk, Malwina; Zindel, Daniel; van Beek, Wouter; Hirsch, Ofer; Kränzlin, Niklaus; Niederberger, Markus; Koziej, Dorota
<x xml:space="preserve">Abstract</x> Closing the loop: initially, the reactivity of benzyl alcohol determines the nucleation of Cu nanoparticles, but as soon as they start to form they begin to catalyze the condensation of benzyl alcohol to dibenzylether.